Lung injury in vivax malaria: pathophysiological evidence for pulmonary vascular sequestration and posttreatment alveolar-capillary inflammation. - Anstey, N; Handojo, T; Pain, M; Kenangalem, E; Tjitra, E; Price, R; Maguire, G (2007)
BACKGROUND: The mechanisms underlying lung injury in vivax malaria are not well understood. Inflammatory responses to Plasmodium falciparum and P. vivax, to our knowledge, have not previously been compared at an organ level. METHODS: Respiratory symptoms and physiological aspects were measured longitudinally in Indonesian adults with uncomplicated vivax (n=50) and falciparum (n=50) malaria. Normal values were derived from 109 control subjects. Gas transfer was partitioned into its alveolar-capillary membrane (D(M)) and pulmonary capillary vascular (V(C)) components, to characterize the site and timing of impaired gas transfer. RESULTS: Mean baseline V(C) volume was significantly reduced in vivax and falciparum malaria, improving with treatment in each species. Baseline D(M) function was not impaired in either species. The progressive deterioration in D(M) function after treatment was statistically significant in vivax malaria but not in uncomplicated falciparum malaria. Oxygen saturation deteriorated after treatment in vivax but improved in falciparum malaria. CONCLUSIONS: The baseline reduction in V(C) volume but not in D(M) function suggests encroachment on V(C) volume by parasitized erythrocytes and suggests that P. vivax-infected erythrocytes may sequester within the pulmonary microvasculature. Progressive alveolar-capillary dysfunction after treatment of vivax malaria is consistent with a greater inflammatory response to a given parasite burden in P. vivax relative to that in P. falciparum.